2011
DOI: 10.1371/journal.pone.0029400
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Food Intake and Body Weight in Mice Deficient for the G Protein-Coupled Receptor GPR82

Abstract: G protein-coupled receptors (GPCR) are involved in the regulation of numerous physiological functions. Therefore, GPCR variants may have conferred important selective advantages during periods of human evolution. Indeed, several genomic loci with signatures of recent selection in humans contain GPCR genes among them the X-chromosomally located gene for GPR82. This gene encodes a so-called orphan GPCR with unknown function. To address the functional relevance of GPR82 gene-deficient mice were characterized. GPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In fact, Dembowski et al [27] recently showed that CASK contains an inducible exon in the GuK domain that is expressed only upon neuronal stimulation. In addition, the mammalian CASK gene locus contains two orphan rhodopsin-like GPCRs (G-protein-coupled receptors) embedded in its introns [28]. It is reasonable to conclude that the increases in intron length seen in the mammalian CASK gene probably contribute to the novel and essential function(s) unique to the CASK protein in mammals through a variety of mechanisms.…”
Section: Gene Sizementioning
confidence: 99%
“…In fact, Dembowski et al [27] recently showed that CASK contains an inducible exon in the GuK domain that is expressed only upon neuronal stimulation. In addition, the mammalian CASK gene locus contains two orphan rhodopsin-like GPCRs (G-protein-coupled receptors) embedded in its introns [28]. It is reasonable to conclude that the increases in intron length seen in the mammalian CASK gene probably contribute to the novel and essential function(s) unique to the CASK protein in mammals through a variety of mechanisms.…”
Section: Gene Sizementioning
confidence: 99%
“…Slices were stained with H&E. Blood cell counting from EDTA blood samples was performed automatically (ScilVet abc; Scil Corporation, Viernheim, Germany). Open field and hot plate tests were performed as reported previously (17) using automated measuring technology (TSE Systems, Bad Homburg, Germany; Hot Plate 602001).…”
mentioning
confidence: 99%
“…SCFA have effects on appetite control and are considered to be important to HDAC inhibition (Figure 3) which is currently an important therapy for AD. SCFA exhibit marked effects on free fatty acid metabolism on binding to G coupled receptors that are involved in appetite control and play an important role in obesity and AD [160][161][162]. SCFA have been shown to have marked effects on insulin sensitivity and lipid metabolism and are associated to the field of insulin resistance syndrome and AD.…”
Section: Open Access Fnsmentioning
confidence: 99%